Silicon-aluminum composite oxide carrier-supported catalyst and preparation method and use thereof
By adding AL-MOF materials to the silica solution, the silicon aluminum composite oxide carrier carrier load catalyst is prepared, the existing catalyst strength and lack of wear resistance have been solved, and the long-term and efficient catalytic performance of the catalysts are achieved.
Patent Information
- Application Number
- CN202310127780.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-17
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-02-17
AI Technical Summary
The existing ammonia oxidation catalysts have problems with insufficient strength and wear resistance in industrial applications, resulting in a short catalyst service life.
By adding AL-MOF materials to the silica solution, the silicon aluminum composite oxide carrier carrier load catalyst is prepared, and the porous structure and high ratio area of the AL-MOF material are used to regulate the structure and performance of the catalyst to improve its strength and abrasion resistance. Essence
It significantly improves the strength and abrasion resistance of the catalyst, prolongs the service life of the catalyst, and improves the activity and selectivity of the catalyst.
Smart Images

Figure BDA0004082659650000091 
Figure BDA0004082659650000092
Abstract
Description
Technical Field
[0001] The present invention relates to a silicon-aluminum composite oxide carrier-supported catalyst and a preparation method and application thereof, which belongs to the technical field of inorganic chemistry and also to the technical field of fine chemicals. Background Art
[0002] Aromatic nitriles, as high value-added fine chemicals, are key raw materials for the manufacture of some highly efficient and low-toxic pesticides, new medicines, high-performance materials, dyes, etc., and are widely used in various fields of the national economy. The general preparation method of aromatic nitriles is through Sandmeyer reaction or through the dehydration of the corresponding aldoxime or the reaction of carboxylic acid and urea. These methods have the disadvantages of difficult raw material sources, long reaction routes, high costs, and high pollution. Aromatic nitriles can also be prepared by ammoxidation reaction using methyl aromatic compounds as raw materials. The ammoxidation method for preparing aromatic nitriles has the advantages of being simple, continuous, strong in production capacity, significant in economic benefits, and environmentally friendly. It is recognized as the most advanced and economical production method. The core is the development of highly active and highly selective ammoxidation catalysts.
[0003] Ammonia oxidation catalysts can be divided into supported and unsupported catalysts according to their composition. Supported catalysts are composed of carriers and active components. They are widely used in industry because of their advantages such as easy preparation, low price, good strength, high activity and long life. The addition of carriers can reduce the amount of active components and reduce production costs on the one hand; on the other hand, it is conducive to the molding of catalysts and facilitates the formation of micron-sized spherical particles; in particular, the carrier can play a structural support role, so that the catalyst has a certain strength and prolongs the service life of the catalyst. In the past, people believed that the carrier was inert and only played a structural support role, which had little effect on the catalytic performance; later, more and more studies showed that the carrier can not only regulate the structure of the catalyst, but also affect the performance of the catalyst. The carrier itself may be inert and have no catalytic activity, but the type of carrier and the preparation process of the carrier and catalyst are different, and different structures of carriers and catalysts can be obtained, thereby regulating the morphology, particle size and surface area of the catalyst; the corresponding action of the carrier and the active species will also affect the crystal phase, distribution, valence, pH and redox properties of the active species, which will greatly affect the performance of the catalyst.
[0004] The carriers used for supported catalysts are generally SiO2, Al2O3, TiO2, etc. SiO2 has become the most commonly used ammonia oxidation catalyst carrier in the industry due to its advantages such as easy preparation, low price, easy structure control and good strength. However, when used for industrial catalysts, its strength and wear resistance need to be further improved. Al2O3 is another commonly used carrier for industrial catalysts. Compared with silica gel supported catalysts, Al2O3 supported catalysts are generally stronger, but the cost is also higher and the molding and processing is more difficult.
[0005] Metal-organic frameworks (MOFs) are a class of porous materials that have received increasing attention over the past two decades. Unlike other porous materials such as zeolites, which are built entirely of inorganic materials, and covalent organic frameworks, which are built entirely of organic compounds, MOFs can be classified as hybrid materials because their frameworks are built with metal nodes or clusters as the inorganic part and organic ligands as linkers. Since the framework contains organic linkers, MOFs have several advantages over other conventional porous materials (zeolites, activated carbon, etc.), such as high surface area, pore functionalization capabilities, and pore size tunability. Aluminum-based metal-organic frameworks (Al-MOFs) are considered to be one of the most promising MOFs due to their excellent framework stability and have been widely studied. In addition, aluminum is a relatively cheap and abundant metal source compared to other metal sources, which makes it an attractive metal source for large-scale production of MOFs.
[0006] A certain amount of Al-MOF material is added to the silica sol, and a silicon-aluminum composite oxide carrier-supported catalyst is prepared by spray drying. The addition of Al-MOF material can improve the strength and wear resistance of the catalyst on the one hand, and further improve the performance of the catalyst through the role of the carrier on the other hand. Summary of the invention
[0007] A technical problem to be solved by the present invention is to provide a silicon-aluminum composite oxide carrier-supported catalyst.
[0008] Another technical problem to be solved by the present invention is to provide a method for preparing the above catalyst.
[0009] The third technical problem to be solved by the present invention is to provide the use of the above catalyst.
[0010] In order to solve the first technical problem mentioned above, the silica-aluminum composite oxide carrier-supported catalyst provided by the present invention is a multi-component vanadium-containing composite oxide supported on a silica-aluminum composite oxide carrier, wherein the silica-aluminum composite oxide carrier is composited by silicon oxide and aluminum oxide, wherein silicon oxide uses silica sol as a precursor, and aluminum oxide uses Al-MOF material as a precursor, and the silica sol precursor and the Al-MOF material precursor are evenly mixed and then calcined at high temperature to form a silica-aluminum composite oxide carrier; wherein the weight percentage of aluminum oxide (i.e., alumina) in the carrier is 1 to 100%, preferably 5 to 80%. The silica sol precursor of silicon oxide can be acidic, alkaline or neutral silica sol; the Al-MOF material precursor of aluminum oxide includes one or more of the following materials: MIL (Materials Institute Lavoisier), CAU (Christian-Albrechts-University), DUT (Dresden University ofTechnology), PCN (Porouscoordinationnetwork) and other types, such as MIL-53, MIL-96, MIL-100, MIL-110, MIL-68, MIL -101-NH2, MIL-12, MIL-14, MIL-27, MIL-32, MIL-34, MIL-64, MIL-69, MIL-91, MIL-116, MIL-118, MIL-120, MIL-121, MIL-122, MIL-160, DUT-4, CAU-1, CAU-3, CAU-4, CAU-6, CAU-8, CAU-10, CAU-10-H, CAU-10-NO2, CAU-10-NH2, CAU-10-OH, CAU-10-CH3, CAU-10-OCH3, CAU-11, CAU-12, CAU-13, CAU-15, CAU-23, Al-fumarate, etc. The composition of the active components in the catalyst is expressed as: VA a B b C c D d E e O x; Wherein A is at least one of titanium, chromium, molybdenum, antimony and phosphorus, B is at least one of boron, manganese, bismuth, tungsten and zirconium, C is cobalt, nickel, copper or zinc, D is lanthanum, cerium, samarium, europium or scandium, and E is at least one of lithium, sodium, potassium, rubidium, cesium, magnesium, calcium, strontium and barium; a = 0.2-2.5, b = 0-1.5, c = 0-1.0, d = 0-0.8, e = 0.01-0.5, and x is determined according to the valence balance of the above elements. The active components are uniformly mixed with the silicon-aluminum composite oxide carrier to form composite microspheres; the sum of the weights of the active components in the catalyst accounts for 10-80% of the total weight of the composite microspheres, preferably 30-70%. The diameter of the composite microspheres ranges from 20 to 120 μm, and the average diameter is 40 to 60 μm.
[0011] On the one hand, the addition of aluminum oxide precursor Al-MOF material can utilize the advantages of MOF materials, such as large specific surface area, special controllable pore structure, etc. to control the structure and morphology of the catalyst, including particle size, specific surface area, pore structure and volume, so as to control the physical, chemical and catalytic properties of the catalyst; on the other hand, it can strengthen the role of the active center and the carrier, reduce the loss of active components, and improve the strength and wear resistance of the catalyst, greatly extending the service life of the catalyst; thirdly, by adding aluminum oxide precursor to form a composite carrier, the ratio and strength of non-protonic acid and protonic acid in the carrier can be controlled, thereby adjusting the acidity and alkalinity of the catalyst, redox ability and coordination ability with the reactants, thereby improving the activity and selectivity of the catalyst.
[0012] In order to solve the above second technical problem, the technical solution designed by the present invention is as follows:
[0013] The present invention adopts a spray drying method to prepare the catalyst, and the specific steps are: firstly, the silicon oxide precursor silica sol and the aluminum oxide precursor Al-MOF material are mixed evenly, and the conversion is formed into the catalyst active component VA a B b C c D d E e O x The precursors are dissolved, mixed and mixed with the above silicon-aluminum oxide precursor (i.e. silicon oxide precursor silica sol and aluminum oxide precursor Al-MOF material) in a certain proportion to form a suspension or slurry; sprayed and formed by a high-speed centrifugal spray dryer, and activated at high temperature after drying to form a micron-sized microsphere silicon-aluminum composite oxide carrier-supported catalyst. The activation temperature is between 350 and 700°C, and the best temperature range is 400 to 600°C. The activation time is 2 to 15 hours, and the best activation time range is 3 to 8 hours.
[0014] Each precursor of the catalyst active component refers to a compound containing at least one element among V, A, B, C, D and E, and the ratio of the sum of the amount of V, the sum of the amount of A, the sum of the amount of B, the sum of the amount of C, the sum of the amount of D and the sum of the amount of E in each precursor is 1:a:b:c:d:e; when b is zero, none of the precursors contains the B element; when c is zero, none of the precursors contains the C element; when d is zero, none of the precursors contains the D element.
[0015] When preparing the catalyst, any precursor can be an oxide, salt, acid or base containing at least one element of V, A, B, C, D and E. For example, V2O5 or NH4VO3 can be used for vanadium; TiCl4, TiCl3 or TiO2 can be used for titanium; Cr(NO3)3·9H2O, Cr2O3, CrO3 or (NH4)2Cr2O7 can be used for chromium; MoO3, (NH4)6Mo7O 24etc.; antimony can be made of Sb2O3, Sb2O5, H3SbO4, HSb(OH)6, Sb(NO3)3, SbCl3, SbCl5, (SbO)2SO4, antimony acetate, ammonium antimony oxalate, potassium antimony tartrate, sodium antimony tartrate or antimony tartrate; phosphorus can be made of H3PO4, (NH4)3PO4, (NH4)2HPO4, (NH4)H2PO4 or P2O5; boron can be made of H3BO3, B2O3, etc.; manganese can be made of MnO2, MnCl2, Mn(NO3)2, etc.; bismuth can be made of Bi(NO3)3, BiCl3, Bi2O3, etc.; tungsten can be made of WO3, WCl6, WOCl4, WO2Cl2, H2WO4 or (NH4)2WO4, etc.; zirconium can be made of ZrCl4, ZrO2 or zirconium acetylacetonate, etc.; cobalt can be made of Co(OAc)2, Co(NO3)2·6H2O, Co3O4 or CoCl2, etc.; nickel can be made of NiCl2·6H2O or Ni(NO3)2·6H2O, etc.; copper can be made of CuO, CuCl2, CuSO4·5H2O, Cu(NO3)2 or Cu(OAc2, etc.; zinc can be made of ZnO, ZnCl2, Zn( NO3)2 or Zn(OAc)2·2H2O, etc.; rare earth lanthanum, cerium, samarium, europium, scandium, etc. can be made of rare earth nitrates, acetates, sulfates, (p-toluene)sulfonates, chlorides, oxides, etc.; lithium can be made of Li2O, LiCl, LiNO3 or Li2CO3, etc.; sodium can be made of Na2CO3, NaHCO3, NaOH, NaCl, NaNO3, Na2SO4, NaOAc or Na2C2O4, etc.; potassium can be made of KOH, KCl, KNO3, K2CO3, K2SO4, KOAc or K2C2O4, etc.; rubidium can be made of R Cesium can be made of CsCl, CsNO3, Cs2CO3, Cs2SO4, CsOAc or Cs2C2O4; magnesium can be made of MgO, MgCl2 or Mg(NO3)2·6H2O; calcium can be made of CaCl2·6H2O, Ca(OH)2 or Ca(NO3)2; strontium can be made of SrCl2, Sr(OH)2 or Sr(NO3)2; barium can be made of BaCl2, Ba(OH)2 or Ba(NO3)2. The solution is prepared by a commonly used method known in the art, for example, V2O5 is dissolved in H2C2O4 aqueous solution to prepare a solution, while KCl, KNO3, K2CO3, etc. are directly dissolved in water to prepare a solution.
[0016] To solve the third technical problem mentioned above, the catalyst provided by the present invention is used for the ammoxidation reaction of methyl aromatic compounds to prepare aromatic nitriles, wherein the methyl aromatic compounds refer to compounds having a methyl group attached to an aromatic ring, and the aromatic ring includes but is not limited to a benzene ring, an aromatic heterocyclic ring such as a pyridine ring, and the like.
[0017] Ammoxidation reaction of methyl aromatic compounds with ammonia and oxygen in the presence of a catalyst produces aromatic nitrile; the reaction yield is 80-98%. Methyl aromatic compounds include toluene, halogenated toluene, xylene, methylpyridine, etc. The optimal process conditions for preparing aromatic nitrile by ammoxidation reaction of methyl aromatic compounds using the above catalyst are as follows: reaction temperature 370-480°C, air to methyl aromatic compound molar ratio 8-60:1, ammonia to methyl aromatic compound molar ratio 1-10:1, catalyst load 10-200g / (kgcat·h). Under a quartz tube fluidized bed reactor with an inner diameter of 30mm and stable reaction conditions, the conversion rate of methyl aromatic compounds can be higher than 98%, and the molar yield of aromatic nitrile can reach 80-98%.
[0018] Compared with other methods, the present invention has the advantages of cheap and readily available reaction raw materials, simple process route, environmental friendliness, low catalyst preparation cost, high ammoxidation reaction yield, etc., especially the catalyst strength and wear resistance are greatly improved, the life is greatly extended, the catalyst activity and product selectivity are also improved. The ammoxidation reaction catalyst has high selectivity and activity; the preparation method is simple, the cost is low, it has good thermal stability and mechanical strength, it can be used in both fixed bed and fluidized bed reactors, and has good application value. DETAILED DESCRIPTION
[0019] The following examples will help to further understand the present invention, but they are not intended to limit the present invention.
[0020] Example 1
[0021] 27g of MOF material MIL-32 (Al) was added to 210g of silica sol with a content of 30% and stirred to form a uniform suspension; 63.90g of H2C2O4·2H2O was dissolved in 300mL of 80℃ distilled water, 30.73g of V2O5 was slowly added to react until no gas was generated, and then 38.93g of 85% H3PO4, 48.22g of Cr(NO3)3, 16.05g of NiCl2·6H2O, and 17.88g of (NH4)6Mo7O were added. 24 ·4H2O and 0.62g Li2CO3, after forming a uniform solution, slowly add it to the mixed suspension of the above silica sol and Al-MOF. After stirring evenly, the catalyst precursor is obtained by high-speed spray centrifugal drying, dried in a muffle furnace at 110°C, and then gradually heated to 500°C and kept warm for 8 hours. After natural cooling, it is ready for use. The active composition of the catalyst is: VP1Cr 0.6 Mo 0.3 Ni 0.2 Li 0.05 O 7.025The active component content is 50%, and the weight percentage of alumina in the silicon-aluminum composite oxide carrier is 30%. The average particle size of the catalyst is 53μm, the bulk density is 0.98g / ml, and the specific surface area is 58m 2 / g, and the wear rate, an indicator of wear resistance, is 1.7% (measured in accordance with the U.S. ASTM D 5757-00 "Standard Test Method for Determining Wear and Erosion of Powder Catalysts Under Air Jet").
[0022] 100 g of the solid catalyst was loaded into a quartz tube fluidized bed reactor with an inner diameter of 30 mm, the molar ratio of the reaction raw materials was: 2,6-dichlorotoluene: NH3: Air = 1:5:15, the reaction temperature was 673±1K, and the catalyst load was 50 g / (kgcat·h). After 8 hours of reaction, the conversion rate of 2,6-dichlorotoluene was 99.1%, and the molar yield of 2,6-dichlorobenzonitrile was 92.5%.
[0023] Example 2
[0024] Comparative Example: The catalyst preparation method is the same as Example 1, except that the MOF material MIL-32 (Al) is not added to the silica sol, the amount of 30% silica sol is 300 grams, and the catalyst active components are the same. The average particle size of the catalyst is 51 μm, the bulk density is 0.93 g / ml, and the specific surface area is 72 m 2 / g, the attrition rate is 2.9%, which is more than 70% higher than that of Example 1; the lower the attrition rate, the better the wear resistance, and the components are less likely to fall off and lose, so the catalyst prepared in Example 1 is more wear-resistant and has greater strength. The experimental conditions for catalytic ammoxidation of 2,6-dichlorotoluene are the same as those in Example 1. After 8 hours of reaction, the conversion rate of 2,6-dichlorotoluene is 98.5%, and the molar yield of 2,6-dichlorobenzonitrile is 86.3%.
[0025] Example 3
[0026] Comparative Example: The catalyst preparation method is the same as that in Example 1, except that the Al-MOF material is replaced with 90g of 30% aluminum sol, and the aluminum oxide content in the catalyst carrier and the catalyst active components are the same as those in Example 1. The catalyst attrition rate is 2.4%, which is more than 40% higher than that in Example 1, indicating that the catalyst strength and wear resistance are not as good as the catalyst obtained by using the Al-MOF material as the carrier precursor. It is used to catalyze the ammoxidation reaction of 2,6-dichlorotoluene. When the reaction conditions are the same as those in Example 1, the conversion rate of 2,6-dichlorotoluene is 98.7%, and the molar yield of 2,6-dichlorobenzonitrile is 88.2%.
[0027] Embodiments 4 to 10
[0028] The relevant physical property parameters of the catalysts prepared in Examples 4 to 10 are close to those in Example 1, and all have good wear resistance.
[0029] Different methyl aromatic compounds, different catalyst formulations and aluminum oxide precursors, and different reaction process conditions. The composition of the catalyst, the catalytic reaction conditions and the reaction results are shown in Tables 1 and 2 below:
[0030] Table 1 Composition of the catalyst used to catalyze the reaction of each methyl aromatic compound in Examples 4 to 10
[0031]
[0032] Table 2 Catalytic reaction conditions and reaction results in Examples 4-10
[0033]
[0034] It is well known to those skilled in the art that the catalyst of the present invention containing other optional components can also be prepared according to the above method. During preparation, the corresponding precursor substances of other optional components can be replaced in proportion with reference to the above embodiments to obtain the desired catalyst. The corresponding precursors of other optional components can be oxides, salts, acids or bases thereof.
Claims
1. A silicon-aluminum composite oxide carrier-supported catalyst, characterized in that: The catalyst is a multi-component vanadium-containing composite oxide supported by a silicon-aluminum composite oxide carrier, wherein the silicon-aluminum composite oxide carrier is composited with silicon oxide and aluminum oxide, wherein silicon oxide uses silica sol as a precursor, and aluminum oxide uses Al-MOF material as a precursor; after the silica sol and Al-MOF material are evenly mixed, they are calcined at high temperature to form a silicon-aluminum composite oxide carrier; the composition of the active component is expressed as: VA a B b C c D d E e O x ; A is at least one of titanium, chromium, molybdenum, antimony and phosphorus, B is at least one of boron, manganese, bismuth, tungsten and zirconium, C is cobalt, nickel, copper or zinc, D is lanthanum, cerium, samarium, europium or scandium, and E is at least one of lithium, sodium, potassium, rubidium, cesium, magnesium, calcium, strontium or barium; a=0.2-2.5, b=0-1.5, c=0-1.0, d=0-0.8, e=0.01-0.5, and x is determined according to the content of the above elements according to the valence balance; The active component is uniformly mixed with the silicon-aluminum composite oxide carrier to form composite microspheres; the weight percentage content of the active component in the catalyst is 10-80%; the diameter of the composite microspheres ranges from 20 to 120 μm, and the average diameter is 40 to 60 μm.
2. The catalyst according to claim 1, characterized in that: The silicon oxide precursor silica sol is acidic, alkaline or neutral silica sol; the aluminum oxide precursor Al-MOF material includes at least one material of MIL, CAU, DUT and PCN types.
3. The catalyst according to claim 1 or 2, characterized in that: The weight percentage of aluminum oxide in the silicon-aluminum composite oxide carrier of the catalyst is 5-80%.
4. The catalyst according to claim 1 or 2, characterized in that: The weight percentage content of the active component in the catalyst is 30-70%.
5. The method for preparing the catalyst according to any one of claims 1 to 4, characterized in that: The preparation method adopts high-speed centrifugal spray drying, and the specific steps are: 1) mixing silicon oxide precursor silica sol and aluminum oxide precursor Al-MOF material uniformly; 2) Convert to the catalyst active component VA a B b C c D d E e O x The precursors are dissolved, mixed and uniformly mixed with the silicon and aluminum oxide precursors to form a suspension or slurry; 3) Spraying into shape by a high-speed centrifugal spray dryer; 4) After drying, high temperature activation is performed to form a micron-sized microsphere-type silicon-aluminum composite oxide carrier-supported catalyst; the high temperature activation temperature is 350-700° C., and the activation time is 2-15 hours; Each precursor of the catalyst active component refers to a compound containing at least one element of V, A, B, C, D and E, and the ratio of the sum of the amount of V, the sum of the amount of A, the sum of the amount of B, the sum of the amount of C, the sum of the amount of D and the sum of the amount of E in each precursor is 1:a:b:c:d:e; When b is zero, none of the precursors contain element B; when c is zero, none of the precursors contain element C; When d is zero, none of the precursors contains the D element.
6. The method for preparing the catalyst according to claim 5, characterized in that: The temperature of the high temperature activation is 400-600° C., and the activation time is 3-8 hours.
7. The method for preparing the catalyst according to claim 5 or 6, characterized in that: The catalyst active component precursor is an oxide, salt, acid or base containing at least one element among V, A, B, C, D and E.
8. The method for preparing the catalyst according to claim 7, characterized in that: The catalyst active component precursor is V2O5 or NH4VO3; TiCl4, TiCl3 or TiO2; Cr(NO3)3·9H2O, Cr2O3, CrO3 or (NH4)2Cr2O7; MoO3, (NH4)6Mo7O 24 ; Sb2O3, Sb2O5, H3SbO4, HSb(OH)6, Sb(NO3)3, SbCl3, SbCl5, (SbO)2SO4, antimony acetate, ammonium antimony oxalate, potassium antimony tartrate, sodium antimony tartrate or antimony tartrate; H3PO4, (NH4)3PO4, (NH4)2HPO4, (NH4)H2PO4 or P2O5; H3BO3, B2O3; MnO2, MnCl2, Mn(NO3)2; Bi(NO3)3, BiCl3 , Bi2O3; WO3, WCl6, WOCl4, WO2Cl2, H2WO4 or (NH4)2WO4; ZrCl4, ZrO2 or zirconium acetylacetonate; Co(OAc)2, Co(NO3)2·6H2O, Co3O4 or CoCl2; NiCl2·6H2O or Ni(NO3)2·6H2O; CuO, CuCl2, CuSO4·5H2O, Cu(NO3)2 or Cu(OAc2); ZnO, ZnCl2, Zn(N O3)2 or Zn(OAc)2·2H2O; nitrates, acetates, sulfates, benzenesulfonates, p-toluenesulfonates, chlorides or oxides of rare earth lanthanum, cerium, samarium, europium or scandium; Li2O, LiCl, LiNO3 or Li2CO3; Na2CO3, NaHCO3, NaOH, NaCl, NaNO3, Na2SO4, NaOAc or Na2C2O4; KOH, KCl, KNO3, K2CO3, K2SO4, KOAc or K2C2O4; R bCl, RbNO3, Rb2CO3, Rb2SO4, RbOAc or Rb2C2O4; CsCl, CsNO3, Cs2CO3, Cs2SO4, CsOAc or Cs2C2O4; MgO, MgCl2 or Mg(NO3)2·6H2O; CaCl2·6H2O, Ca(OH)2 or Ca(NO3)2; SrCl2, Sr(OH)2 or Sr(NO3)2; BaCl2, Ba(OH)2 or Ba(NO3)2.
9. Use of the catalyst according to any one of claims 1 to 4, characterized in that: The catalyst is used for the ammoxidation reaction of methyl aromatic compounds to prepare aromatic nitrile.
10. Use of the catalyst according to claim 9, characterized in that: The methyl aromatic compounds include toluene, halogenated toluene, xylene and methyl heterocyclic aromatic compounds.
Citation Information
Patent Citations
Aromatic ammoxidation fluidized bed catalyst, preparation method and application
CN106268890A